Retroculus acherontos, a new species of cichlid fish (Teleostei) from the Rio Tocantins basin - Landim, Maria Isabel; Moreira, Cristiano R.; Figueiredo, Carlos A. (Zootaxa, 2015)
Retroculus acherontos is described from the Rio Tocantins basin, Brazil. It is distinguished from all congeners by the presence of a nuchal hump in large specimens, an irregular black blotch located on the middle of the anterior soft dorsal-fin rays, fewer pectoral-fin rays (15–16), a deeper body, a convex ventral profile, a more transversely convex ventral surface of the body, and by chest scales similar in size to the scales on the side. An expanded diagnosis for the genus Retroculus is provided.